Prescribing habits and caregiver satisfaction with resources for dosing children: Rationale for more informative dosing guidance - Zuppa Athena F; Patel Dimple; Narayan Mahesh; Barrett Jeffrey S; Adamson Peter C (BMC, 2011)
Abstract Background Physicians, nurses and hospital pharmacists were surveyed to assess attitudes of hospital-based pediatric caregivers regarding the dosing of medicine to children. Our objectives were to gauge how current resources are utilized to guide the management of pediatric pharmacotherapy, assess drugs and drug classes where guidance is most critical and examine the prevalence and practice of dose adjustment in pediatric patients. Methods Questionnaire categories included demographics, pharmacotherapy resources, dosing adjustment and modification, and valuation of additional tools to provide improved pharmacotherapy guidance. The questionnaire was developed in collaboration with representative nurse, pharmacist and physician team members using the SurveyMonkey.com site and survey tool. The survey link was distributed to caregivers via email. The questionnaire results of 303 respondents were collected into MS Excel and imported into SAS for data summarization. Results A total of 313 responses were obtained. Physician and nurse practitioner groups comprised the majority of the responses. Approximately 80% of the responders considered dosing adjustment important in pediatric pharmacotherapy. While there was general satisfaction with available resources, nearly 75% responded in support of access to predictive tools that facilitate individualized patient pharmacotherapy. The majority of respondents (> 65%) indicated that dosing outside standard practice occurs in 1-20% of their patients, while still a substantial number of respondents (a range of 8 to 20% reflecting the resident and fellow categories) estimated between 20 and 50% of their patients required adjustments outside the standard practice. Conclusions Differences in prescribing habits based on caregiver role, specialty and location were small and likely require further exploration. Existing resources are generally viewed as helpful but inadequate to guide recommendations for individual patients. Decision support systems connected to hospital-based electronic medical records offer the promise of informative and individualized pharmacotherapy guidance.